Democratic trajectories in Africa : unravelling the impact of foreign aid - Resnick, Danielle; Van de Walle, Nicolas (Studies in development economics., 2013)
This volume examines how foreign aid has influenced democratic transitions and consolidation in sub-Saharan Africa.